The role of Political Opposition in the Era of Turkish Justice and Development Party - Muwafaq Adil OMAR (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The political opposition in Turkey, since the founding of the Turkish Republic, has faced a real crisis, as it has not been able to achieve its goals and perform its functions in the required manner, due to the deep-rooted cultural and historical orientation among members of Turkish society, which is a lack of criticism of the authority and the government. Since 2002, with the arrival of the Justice and Development Party to power, the political opposition has not succeeded in changing the ruling party since it came to power until now, despite resorting to taking many pressure means such as organizing peaceful demonstrations, criticizing the government’s policies in Parliament, and exploiting the poor economic and financial conditions. And criticizing the presence of Syrian and Afghan refugees in Turkey. But with the change of the country’s political system and the start of the new presidential system since 2018, a clear change appeared in the mechanism of action of the opposition parties, according to this new system, the need to form electoral coalitions in order to reach power due to the inability of political parties to obtain percentages that guarantee them Winning the presidential and parliamentary elections. In addition, the opposition parties were able to achieve an important victory in the local elections that took place in 2019, as the opposition parties' candidates won the presidency of major municipalities such as Istanbul and Ankara. This step encouraged the opposition forces to work to unify their discourse and increase the percentage of coordination among them. In light of these developments, the Six-Party Table was formed by six opposition parties. Despite all these developments and the important steps taken by the opposition parties, the capabilities and means in the hands of the Justice and Development Party and its ally, in addition to the charisma of the personality of Recep Tayyip Erdogan, must be taken into consideration in the upcoming elections.